Pengaruh asssurance, tangible dan reliablity untuk meningkatkan kepuasan pasien pada puskesmas Lapai - Utami, Hayu Yolanda; Natassia, Rizky (Jurnal Kajian Manajemen Bisnis, 2019)
The purpose of this study was to see influence the effect of Assurance, tangible and reliability of patient satisfaction at the Lapai Public health. This type of research is associative, this research using multiple regression analysis. The population in this study were all patients who used services at the Lapai Public Health. The sample in this study amounted to 30 people who were taken using accidental sampling technique. The results showed that all assurance, tangible and reliability had a positive and significant effect on patient satisfaction at the Lapai Public health. Keywords: Assurance; tangible; Â reliability; satisfaction